An assessment of the regional net water demand for irrigation development of the upper Berg River area based on agroclimatological observations - Du Pisani, Andries Lourens (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D. Agric.) -- University of Stellenbosch, 1974.